A plethora of manifestations following a Mycoplasma pneumoniae infection: a case report. Issue 3 (3rd May 2020) - Matthys, Imke; Borsboom, Daniel; Steyaert, Sophia; Vervloet, Delphine; Cornelis, Kristoff; Vanderstraeten, Erik; Kindt, Sébastien; Dewint, Pieter; Lambrecht, Valerie; Sinnaeve, Peter; Van Steenkiste, Christophe
ABSTRACT: Mycoplasma pneumoniae infection can present with a plethora of symptoms and result in a systemic vasculitis by activating a cascade of autoimmune reactions. In this case report, a young man without relevant past medical history was admitted to the hospital with diarrhea, abdominal pain and spiking fever. A CT-scan showed terminal ileitis. A 5-day broad spectrum antibiotic treatment (ciprofloxacin/clindamycin) did not result in any clinical improvement. On the contrary, the patient developed a cholestatic hepatitis, bilateral anterior uveitis and a dry cough. Extensive serological testing finally led to the diagnosis of a M . pneumoniae infection by paired serology (≥4-fold rise in IgG titer). In the diagnostic work-up, a PET-CT was performed and showed increased tracer uptake in the carotids and vertebral arteries, suggesting the diagnosis of vasculitis. After start of azithromycin and low-dose corticosteroids (0.5 mg/kg/day), a gradual clinical and biochemical improvement was observed. But subsequently, the patients relapsed and presented with an acute coronary syndrome. Coronary angiography revealed aneurysmatic deformation of the three coronary arteries, leading to the assumption of coronary vasculitis. Clinical improvement was achieved with high-dose corticosteroids (1 mg/kg/day). This case shows that M . pneumoniae is not merely a pulmonary infection, but that its primary symptoms can be diverse and misleading. All clinicians should be aware of its extrapulmonary manifestations.